(untitled) (Palíndromo, 2024)
This article reflects on the relationships between artistic production and the experience of dying through a case study of the cultural context of the theatricality of social life in Ancient Rome. To do so, we review how such theatricality was socially configured between the strictly scenic presentations and the funeral rites of the Roman aristocracy, public events marked by the use of imagines (extremely realistic wax masks of the dead). From the events surrounding the figure of Julius Caesar to those related to Nero, therefore from the fall of the Republic to the end of the Julio-Claudian dynasty. In this way, we aim to examine from a broader perspective how, after all, these masks established themselves as the foundation of the Roman theory of visual arts, as we find it exposed in the work of Pliny the Elder.